IMPLEMENTASI KEBIJAKAN PENGEMBANGAN RUANG TERBUKA HIJAU DI KOTA ADMINISTRASI JAKARTA BARAT - Annaya Raisha Firmansyah; Supratiwi Supratiwi (Journal of Politic and Government Studies, 2026)
Green Open Space (RTH) is a crucial component for urban environmental sustainability and community quality of life. However, West Jakarta Administrative City has the lowest RTH achievement in DKI Jakarta, reaching only 1.53% of the total area, far from the statutory target of 30%, with no addition of RTH area since 2019. This study aims to analyze the implementation of RTH development policy based on Governor Regulation Number 9 of 2022 and identify obstacles occurring in the field. The research employs a descriptive qualitative method using George C. Edward III's policy implementation model approach, encompassing four indicators: communication, resources, disposition, and bureaucratic structure. Data were collected through in-depth interviews, observations, and documentation studies. The results of the study show that the implementation of Green Open Space development in the West Jakarta Administrative City has not been carried out properly due to top-down policy communication with limited socialization, very minimal financial resources (0.1% of the total regional budget) without a land acquisition budget since 2019, weak executive disposition when dealing with economic interests, and a fragmented bureaucratic structure with coordination dependent on leadership intervention. This shows that implementation barriers are not isolated but multidimensional and systemic. The conclusion of this study confirms that the root of the problem is not merely technical, but rather the absence of political will to make green spaces a priority. Therefore, it is necessary to reallocate the budget based on regional priorities, enforce strict laws against spatial planning violations, and improve cross-sector coordination mechanisms.